1976
DOI: 10.1002/he.36919761603
|View full text |Cite
|
Sign up to set email alerts
|

Structuring the environment to improve outcomes

Abstract: The college environment can be changed to promote student progress, but success requires hard thinking and careful planning about six related questions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1980
1980
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Astin, 1977Astin, , 1993Endo and Harpel, 1982;Pace 1984Pace , 1990Terenzini & Wright, 1987). This approach is used because it generates data that are consistent with measures of actual outcomes (Baird, 1976). Pace (1990) advanced five reasons to accept the validity of student self-reports of cognitive achievement: a) consistency of results over time and across different populations, b) the fact that patterns of outcomes vary for self-reports across majors and length of study in the same manner as has been established through direct achievement testing, c) the internal consistency of questionnaire responses across different items on the same dimension, d) the fact that reported growth follows expected patterns of experience, and e) apparent student seriousness and engagement with the instrument itself.…”
Section: Self-report Measurementmentioning
confidence: 98%
“…Astin, 1977Astin, , 1993Endo and Harpel, 1982;Pace 1984Pace , 1990Terenzini & Wright, 1987). This approach is used because it generates data that are consistent with measures of actual outcomes (Baird, 1976). Pace (1990) advanced five reasons to accept the validity of student self-reports of cognitive achievement: a) consistency of results over time and across different populations, b) the fact that patterns of outcomes vary for self-reports across majors and length of study in the same manner as has been established through direct achievement testing, c) the internal consistency of questionnaire responses across different items on the same dimension, d) the fact that reported growth follows expected patterns of experience, and e) apparent student seriousness and engagement with the instrument itself.…”
Section: Self-report Measurementmentioning
confidence: 98%
“…Researchers have investigated the ecologies of admissions centers (Williams, 1986), counseling centers (Banning, 1989a; Conyne et al, 1979), college student unions (Banning, 2000), and residence halls and housing (Banning, 1995b; Clemons, McKelfresh, & Banning, 2005). Overall, studies have shown that student-centered campus spaces positively affect retention (Banning, 1984), student success (Baird, 1976), and involvement (Banning, 1989c; Kuh & Schuh, 1991).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The contribution of self-efficacy to academic performance is well developed in the literature (Bryan & Bryan, 1981;Chemer, Hu & Gracia, 2001;Hampton & Mason, 2003). In line with this, a handful of studies (Baird, 1976;Ethington & Smart, 1986;Issac et al, 1992;Malaney & Issac, 1988) suggest that students with greater academic achievement and greater academic and social integration at their undergraduate institution are the most likely to pursue graduate studies (Kallio, 1995). Morover, Kalmijn and Kraaykamp (1996) argued that children familiar with cultural and social activities cope well with the subject matter taught in higher levels of education, and they are believed to be more familiar with abstract and intellectual concepts.…”
Section: Theoretical Frameworkmentioning
confidence: 79%